2013
DOI: 10.4049/jimmunol.1201828
|View full text |Cite
|
Sign up to set email alerts
|

Paraoxonase-1 Suppresses Experimental Colitis via the Inhibition of IFN-γ Production from CD4 T Cells

Abstract: Crohn’s disease (CD) is a chronic inflammatory disorder of the gastrointestinal tract, where excessive Th1 cell responses are observed. We performed experiments to identify immunologically bioactive proteins in human plasma and found that paraoxonase (PON)-1, which has esterase activity and is associated with high-density lipoproteins, inhibited the IFN-γ production by both murine and human differentiating Th1 cells. Trinitrobenzene sulfonic acid–induced colitis was attenuated by the administration of PON-1. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 64 publications
2
7
0
Order By: Relevance
“…Therefore, we believe that the colitis amelioration after MSC treatment may be correlated with the control of inflammatory responses upon direct or indirect modulation of the recipient's T reg . Yamanishi et al [50] have shown that the induction of forkhead box protein 3 (FoxP3) + CD4 + CD25 + cells improves experimental colitis, corroborating our findings. Moreover, although we have not observed higher expression of FoxP3 in mice treated with MSC, the increase of other markers of T reg is in agreement with the hypothesis that infused MSC may have promoted immunoregulation and controlled the intestinal response in animals with colitis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, we believe that the colitis amelioration after MSC treatment may be correlated with the control of inflammatory responses upon direct or indirect modulation of the recipient's T reg . Yamanishi et al [50] have shown that the induction of forkhead box protein 3 (FoxP3) + CD4 + CD25 + cells improves experimental colitis, corroborating our findings. Moreover, although we have not observed higher expression of FoxP3 in mice treated with MSC, the increase of other markers of T reg is in agreement with the hypothesis that infused MSC may have promoted immunoregulation and controlled the intestinal response in animals with colitis.…”
Section: Discussionsupporting
confidence: 91%
“…In agreement, MSC administration alleviates TNBSinduced murine colitis by correcting Th1/Th17/T reg imbalances [47]. Yamanishi et al [50] have shown that the induction of forkhead box protein 3 (FoxP3) + CD4 + CD25 + cells improves experimental colitis, corroborating our findings. Therefore, we believe that the colitis amelioration after MSC treatment may be correlated with the control of inflammatory responses upon direct or indirect modulation of the recipient's T reg .…”
Section: Discussionsupporting
confidence: 90%
“…CD is a T helper 1- (Th1-) mediated disease, with overproduction of IFN- γ and IL-12 [ 14 , 15 ]. It is commonly thought that IL-12-mediated Th1 cell transmural colitis induced by trinitrobenzenesulfonic acid (TNBS) causes immunopathological human CD [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The level and the activity of circulating PON1 are also considered as novel biomarkers for the evaluation of these diseases in humans [2226]. Animals deficient in PON1 have been found to be more susceptible to these disease conditions and the overexpression of h-PON1 or administration of purified PON1 in these animals has been shown to prevent/retard the development of these disease conditions [10, 12, 2730]. The beneficial role of h-PON1 in OP-poisoning is also well demonstrated.…”
Section: Protective Role Of Pon1 and Pon1 As A Potential Therapeutmentioning
confidence: 99%